Effect of black soldier fly larvae frass application on pechay (Brassica papa L. var. chinensis (L.) Hanelt) under drought stress - Lor, Sheena Claire R. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Black soldier fly (BSF) farming is a growing industry worldwide that can aid in organic waste processing by converting wastes into a high-nutrient biofertilizer. Fertilizer application has shown to promote soil fertility, plant growth, and plant resistance to abiotic stress. However, it is unclear whether BSF larvae frass application would reduce the negative effects of drought. This study employed a 5 × 3 complete factorial experiment in a randomized complete block design to investigate the potential of BSF larvae frass on reducing the harmful effects of drought stress on pechay (Brassica rapa L. var. chinensis (L.) Hanelt) growth. There were five soil-BSF larvae frass combinations (100 % soil + 5 g NPK; 100 % soil; 95 % soil + 5 % BSF larvae frass; 90 % soil + 10 % BSF larvae frass; 85 % soil + 15 % BSF larvae frass), and three drought stress levels (100 % water holding capacity; 60 % water holding capacity; 30 % water holding capacity) simulated using gravimetric methods. Pechay growth was assessed by new leaf formed, total leaf area (cm2), root and shoot length (cm), and dry weight (g). Analysis of variance showed that drought and BSF larvae frass have independent effects on pechay aboveground and belowground growth. Five percent (5%) BSF larvae frass could be an alternative to inorganic fertilizers under drought stress conditions and may reduce the negative effects of drought. Pechay treated with 15 % BSF larvae frass was most sensitive to moderate and severe drought stress. Under well-watered conditions, at most 15% BSF larvae frass could be an alternative to inorganic fertilizer. The results showed that BSF larvae frass is a promising biofertilizer that could play a critical role in global food security during drought but more research is needed on composting of BSF larvae frass.